New species of freshwater crab genus Kingsleya Ortmann, 1897 (Decapoda: Brachyura: Pseudothelphusidae) from Piauí, northeastern Brazil - Pralon,Bruno (2020)
Abstract A new species of freshwater crab, Kingsleya parnaiba n. sp., collected in a tributary stream of the Parnaíba River Basin in Brazil, is described and illustrated. Kingsleya parnaiba n. sp. morphologically resembles Kingsleya attenboroughi Pinheiro and Santana, 2016 and Kingsleya gustavoi Magalhães, 2005, from which it can be separated by a set of characters of the first gonopod, chelipeds, and female abdomen.